Superb strength and high plasticity in laves phase rich eutectic medium-entropy-alloy nanocomposites. (July 2018) - Ding, Z.Y.; He, Q.F.; Wang, Q.; Yang, Y.
Abstract: Laves phase and laves-phase based conventional composites usually show extreme brittleness at room temperature due to poor fracture toughness. However, in this work, we design a FeCoNiNb0.5 medium-entropy-alloy nanocomposite which possesses a high volume fraction (>50%) of a cubic laves phase but shows superb strength and excellent malleability at room temperature. This high mechanical performance results from the formation of an in-situ nano-scale lamellar structure that joins the hard cubic laves phase and soft medium entropy face-centered cubic (FCC) phase through a semi-coherent interface. When the size of the lamellar structures is tuned below a critical value, this nanocomposite exhibits strong and sustainable strain hardening, leading to a fracture strain over 20% and fracture strength over 3.5 GPa in conventional compression. The mechanism for the unusual strain hardening in the laves-phase rich nanocomposite is explored afterwards with micromechanical experiments and theoretical modeling, which unveils a size-controlled transition in the plasticity mechanism from dislocation slip to twinning in the nano-scale laves phase. Our current work demonstrates that, through mixing a set of carefully selected elements, one can obtain high performance dual-phase eutectic nanostructures which are promising for structural applications. Graphical abstract: Image 1 Highlights: An eutectic medium-entropy-alloy nanocomposite containing over 50% C15 Laves phase was developed. The nanocomposite exhibited superb strength and high plasticity at room temperature. A dislocation based theoretical model was developed for the yielding of the nanocomposite. The micro-scale deformation mechanisms of the nanocomposites were fully examined. The size-controlled deformation mechanism in the nanocomposites was revealed.